Efficacy of a remote virtual reality and EEG enabled psychotherapy system for the treatment of depressive symptoms - Tacca, Christopher; Kerr, Barbara A.; McLamb, Christopher; Ridgway, Kaylie Lyons; Friis, Elizabeth A. (Frontiers in Virtual Reality, 2024)
More than 40% of the U.S. population have experienced mental health disorders since the COVID-19 pandemic. 40% of this group received no treatment for their mental illness. Barriers to treatment include stigma, prohibitive cost, and a belief that treatment is inaccessible, particularly in isolated or rural communities. A novel remote, EEG-enhanced VR psychotherapy system was assessed for its presence and restorativeness, and therapeutic efficacy in improving mood with a single session positive solution-focused session. Thirty adults experiencing depressive symptoms were randomly assigned to either a single session Positive Solutions Focused counseling treatment via Zoom videoconferencing, or the EEG enabled VR psychotherapy system. Participants rated the environment in the VR-EEG therapy as more restorative than Zoom counseling, t = 2.928, p <.004, Cohen's d =.259, and comparable to the Zoom session in presence. The VR-EEG system performed comparably to Zoom online counseling in clients' session ratings of depth and smoothness and client reactions, positivity, and arousal. For a treatment to be considered empirically supported, and therefore valid for use in psychotherapy, it must have equal or greater efficacy than a standard treatment or format. VR-EEG, therefore, has promise as a positive, solution-focused, brief therapy for isolated clients with depressive symptoms.